Development of simple multilevel inverter using voltage regulator IC - Rosnazri, Ali; Soib, Taib, Prof. Madya Dr.; Risnidar Chan Bahaudin; Dina Maizana, Maiz Ahmad; Syafruddin, Hasan (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.